MECHANICAL PROPERTIES OF BIOLOGICAL TISSUES - Begisheva Nailya Rinadovna (Modern American Journals, 2025)
This article studies the active and passive mechanical properties of biological tissues. Biological tissues are analyzed as composite materials with pronounced viscoelastic properties. The mechanical properties of bone, skin, muscle, and vascular tissues are described in detail. The main mechanical models and analytical relationships used to quantitatively describe the deformation of biological structures are presented. The practical importance of studying the mechanical properties of tissues for various fields of medicine is shown.